2021
DOI: 10.1111/jace.17839
|View full text |Cite
|
Sign up to set email alerts
|

A low‐permittivity microwave dielectric ceramic BaZnP2O7 and its performance modification

Abstract: The past few decades have witnessed an ever-growing scholarly interest in microwave dielectric ceramics with the rapid development of telecommunication. [1][2][3][4] Recently, there is a strong ongoing search for dielectric ceramics with a dielectric constant (ε r ) less than 15, a low dielectric loss (tan δ = 1/Q), and a near-zero temperature coefficient (τ f ) to meet the demands for microwave substrate applications. 5,6 Although traditional inorganic substrates such as Al 2 O 3 possess excellent dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Appropriate dielectric properties of ceramics are the premise behind the performance and also determine the characteristics of temperature robustness of a metamaterial perfect absorber. [64][65][66][67] Here, the modification of BENT-AG ceramics is done for hightemperature stable perfect absorption. The results of X-ray diffraction (XRD) and scanning electron microscopy (SEM) are presented in the ESI † (in Fig.…”
Section: Esi †)mentioning
confidence: 99%
“…Appropriate dielectric properties of ceramics are the premise behind the performance and also determine the characteristics of temperature robustness of a metamaterial perfect absorber. [64][65][66][67] Here, the modification of BENT-AG ceramics is done for hightemperature stable perfect absorption. The results of X-ray diffraction (XRD) and scanning electron microscopy (SEM) are presented in the ESI † (in Fig.…”
Section: Esi †)mentioning
confidence: 99%
“…A 2 P 2 O 7 , A 1 A 2 P 2 O 7 (A = Ca, Ba, Sr, Mg, Mn, Zn; A 1 = Ca, Sr, Ba; A 2 = Cu, Zn, Mg), and LiMPO 4 (M = Mg, Zn) [13][14][15][16][17][18][19][20][21][22][23][24][25][26] are some of the hot studied phosphate microwave dielectric ceramics as they possess low dielectric constants, high quality factors, and low sintering temperatures (<950 • C) that meet the LTCC processes. Various reports on LiMPO 4 can be found in the literature, 13,14 and the later studies have mainly focused on ionic substitution to improve the microwave dielectric properties of ceramics [15][16][17][18][19][20] ceramics have superior properties compared to some of the LiMPO 4 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al 25 initially reported that the microwave dielectric properties of BaZnP 2 O 7 are (ε r = 8.4, Q × f = 27 925 GHz and τ f = −56.7 ppm/ • C). Then Chen et al 26 substituted Mg 2+ for Zn 2+ to improve the microwave dielectric properties of ceramics, and based on the P-V-L theory, the relationship between the chemical bond characteristics and performance was analyzed. The excellent performance was realized for the sample BaZn 0.98 Mg 0.02 P 2 O 7 with ε r = 8.21, Q × f = 84 760 GHz and τ f = −21.9 ppm/ • C. However, as can be seen from previously reported works, there are few relevant studies on the spectral and vibrational properties of BaZnP 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Therefore, controlling the near-stoichiometric ratio of BN elements, reducing crystal defects, and improving BN fiber's crystallization and orientation are beneficial to further increase the fiber strength, thermal stability, and transparent properties. [11][12][13][14] However, according to the previous research on the synthesis of precursor polymers and pyrolysis mechanism, most polyborazine precursors are nitrogen-rich, and a large number of N elements will be excessive in the process of carbon removal in an ammonia atmosphere and crystallization in a nitrogen atmosphere, resulting in the content of boron and nitrogen deviating from stoichiometry. 11,[15][16][17] Thus, many B vacancy defects are produced in the crystallization process, which destroys the crystal structure of the fiber and reduces the strength of the fiber.…”
Section: Introductionmentioning
confidence: 99%